Implementasi Media Teka-Teki Silang dalam Meningkatkan Maharah Kitabah Siswa Kelas X MA Darul Ulum Waru - Azizah Nur Kholifah; Nala Avivatun Nafi'ah; Evi Alfiatur Rohmah; Farihatul 'Azizah; Nur Rohmah Khumaidah; Ainun Syarifah; Ahmad Marbuhin; Khoiro Ummatin (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2023)
The lack of varied media usage leads to students feeling bored and experiencing difficulties in understanding lessons, especially in learning the Arabic language. Learners often struggle to master writing skills, including letter formation, sentence construction, and providing the appropriate diacritical marks. Crossword puzzles are among the alternatives that can be employed to enhance students' Arabic writing skills. The purpose of this research is to assess the outcomes of implementing crossword puzzle media to improve the Arabic writing skills of 10th-grade students at MA Darul Ulum Waru. For this study, the author utilized a qualitative approach, specifically the Classroom Action Research (CAR) method. The author employed descriptive research due to its focus on presenting a detailed and clear depiction of the research object. Data analysis involved data reduction to sift through valid information pertinent to the research objectives. The findings revealed increased interest and enthusiasm among 10th-grade students at MA Darul Ulum Waru in engaging with Arabic language learning. This media contributed to enhancing the students' writing proficiency, particularly in school-related vocabulary. Furthermore, it improved memory retention and fostered collaboration among students in completing tasks or missions.